THE RELATIONSHIP OF DRIVER BEHAVIOR AND RISK OF ACCIDENTS IN COAL TRANSPORT TRUCK DRIVERS - Andriana Marwanto; Dhea Egitania Fauzila; Riang Adeko (Proceeding B-ICON, 2023)
The death rate caused by road traffic accidents in Indonesia is still quite high, where some of these accidents involve trucking vehicles. The aims of this research was to determine the relationship between behavior and the risk of accidents in coal transport truck drivers at PT. X. The type of research used is analytical descriptive with a cross sectional approach. The study population was coal hauling truck drivers working at PT. X with a total sampling of 44 respondents. Based on the results of the study, it was found that most (75.0%) drivers have good knowledge; More than half (54.4%) of drivers are supportive of driving behavior; More than half of drivers (63.6%) have good measures against the risk of workplace accidents in coal truck drivers; And more than half of drivers (59.1%) are at risk of workplace accidents. There was no significant relationship between driver behavior, knowledge, attitudes and actions towards occupational accident risk in coal truck drivers. Insignificant research results cannot reduce the importance of risk control in the company because accidents risk death. To reduce the accident rate among truck drivers, it is necessary to provide facilities to increase intensive education and safety training.